Understanding meaning and characteristics of civic development in higher education - Ahrari, Seyedali; Othman, Jamilah; Hassan, Md Salleh; Abu Samah, Bahaman; D' Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2014)
Higher education is a central part of youth life, and its job is to prepare young people to engage in civil society. It is also important in constructing competencies and helping young people to develop a civic identity. Thus, the aim of this study is to explore the meaning and characteristics of civic development among students in the higher education system. A qualitative study using a semi-structural interview is conducted to collect data from 12 international postgraduates of Universiti Putra Malaysia, and the data establishes that three distinct but connected themes-that is, civic knowledge, tendency, and engagement-are key aspects of civic development. The findings relating to these three themes underline the requirements for a civically engaged youth. The findings suggest that policy makers should redesign civic programs based on suitable methods by which to educate students in formal and informal manners.